The song of Innana and Išme-Dagan: an edition of BM 23820+23831 - Ludwig, M; Metcalf, C (De Gruyter, 2017)
This article offers a first edition of BM 23820+23831, a manuscript of a previously unknown Old Babylonian Sumerian poem on the relationship between the goddess Innana and king Išme-Dagan of Isin. The king is initially depicted as a humiliated supplicant who suffers under Innana’s wrath, until the intervention of his personal god restores Innana’s favour. A mythological catalogue lists other individuals and places who offended the goddess and were destroyed by her in retribution.